Percepción ciudadana y expectativas de cambio en la ciudad post-Covid-19: un análisis comparado - Alfaya, Luciano G. (2021)
AbstractThis work analyses the global results obtained by conducting an online survey of more than 12 thousand participants located in nine Latin American countries (Argentina, Brazil, Colombia, Chile, Ecuador, Spain, Mexico, Peru and Portugal). The analysis, segmented by age groups, focus on contrasting, on the one hand, the wishes for change in relation to a series of urban and socio-political issues aimed at the reconstruction of the post-covid city and, on the other, the expectations that this change actually takes place. Thus, a comparative framework between America and Europe is established with evident implications not only in the analysis of the different contemporary urban configurations but also in how public policies have managed the spatial dimension of the pandemic and what has been the public perception in this regard. In addition, this work brings to the table relevant issues and perspectives in relation to the future post-pandemic scenario by suggesting elements and certain perspectives that should be integrated into urban planning and the way of understanding cities.